Development and Characterization of a Sucrose Microneedle Neural Electrode Delivery System. Issue 2 (29th December 2017) - Apollo, Nicholas V.; Jiang, Jonathan; Cheung, Warwick; Baquier, Sebastien; Lai, Alan; Mirebedini, Azadeh; Foroughi, Javad; Wallace, Gordon G.; Shivdasani, Mohit N.; Prawer, Steven; Chen, Shou; Williams, Richard; et al.
Abstract: Stable brain–machine interfaces present extraordinary therapeutic and scientific promise. However, the electrode–tissue interface is susceptible to instability and damage during long‐term implantation. Soft, flexible electrodes demonstrate improved longevity, but pose a new challenge with regard to simple and accurate surgical implantation. A high aspect ratio water‐soluble microneedle is developed based on sucrose which permits straightforward surgical implantation of soft, flexible microelectrodes. Here, a description of the microneedle manufacturing process is presented, along with in vitro and in vivo safety and efficacy assessments. Successful fabrication requires control of the glass transition temperature of aqueous sucrose solutions. The insertion force of 5 different microneedle electrode vehicles is studied in agarose brain phantoms, with the sucrose microneedle eliciting the lowest insertion force and strain energy transfer. Short‐ and long‐term assessments of the pathological response to sucrose microneedle implantations in the brain suggest minimal tissue reactions, comparable to those observed following stainless‐steel hypodermic needle punctures. Finally, microelectrodes fabricated from graphene, carbon nanotubes, or platinum are embedded in sucrose microneedles and implanted into an epileptic rat model for 22 d. All electrodes are functional throughout the implantation period, with the graphene electrode exhibiting the largest seizure signal‐to‐noise ratio and only modest changes in impedance. Abstract : Brain‐machine interfaces have revolutionized both the treatment and study of nervous system disorders. However, hardware issues limit the long‐term utility of these devices due, in part, to their stiffness and size. Soft, flexible electrodes have shown great promise, but they present a surgical challenge. This work describes a system to implant soft, flexible microelectrodes can using water‐soluble sucrose microneedles.